Neuronal Dysfunction and Behavioral Abnormalities Are Evoked by Neural Cells and Aggravated by Inflammatory Microglia in Peroxisomal β-Oxidation Deficiency - Beckers, Lien; Stroobants, Stijn; D’Hooge, Rudi; Baes, Myriam (Frontiers in Cellular Neuroscience, 2018)
It is becoming evident that microglia, the resident immune cells of the central nervous system (CNS), are active contributors in neurological disorders. Nevertheless, the impact of microgliosis on neuropathology, behaviour and clinical decline in neuropathological conditions remains elusive. A mouse model lacking multifunctional protein-2 (MFP2), a pivotal enzyme in peroxisomal β-oxidation, develops a fatal disorder characterized by motor problems similar to the milder form of human disease. The molecular mechanisms underlying neurological decline in men and mice remain unknown. The hallmark of disease in the mouse model is chronic proliferation of microglia in the brain without provoking neuronal loss or demyelination. In order to define the contribution of Mfp2-/- neural cells to development of microgliosis and clinical neuropathology, the constitutive Mfp2-/- mouse model was compared to a neural selective Nestin-Mfp2-/- mouse model. We demonstrate in this study that, in contrast to early-onset and severe microgliosis in constitutive Mfp2-/- mice, Mfp2+/+ microglia in Nestin-Mfp2-/- mice only become mildly inflammatory at end stage of disease. Mfp2-/- microglia are primed and acquire a chronic and strong inflammatory state in Mfp2-/- mice whereas Mfp2+/+ microglia in Nestin-Mfp2-/- mice are not primed and adopt a minimal activation state. The inflammatory microglial phenotype in Mfp2-/- mice is correlated with more severe neuronal dysfunction, faster clinical deterioration and reduced life span compared to Nestin-Mfp2-/- mice. Taken together, our study shows that deletion of MFP2 impairs behaviour and locomotion. Clinical decline and neural pathology is aggravated by an early-onset and excessive microglial response in Mfp2-/- mice and strongly indicates a cell-autonomous role of MFP2 in microglia.